Risk, delegation, and project scope - Andreas Roider (Institute for the Study of Labor (IZA), 2007)
This paper studies a partial-contracting model where an agent may provide effort to increase a project's scope before some later decisions have to be taken. Consistent with existing empirical evidence, we find a positive relationship between exogenous risk and delegation. That is, we show that only if exogenous risk is sufficiently large, the risk-neutral principal may prefer to delegate authority over decisions to the risk-averse agent. Intuitively, for incentive reasons, the principal may optimally want to allow the agent to reduce his risk exposure. Nevertheless, even endogenous risk may be higher when the risk-averse agent has control.
Keywords: 330; Delegation; authority; risk; partial contracting; Kooperative Führung; Agency Theory; Risiko; Unvollständiger Vertrag; Zeitökonomik; Theorie